2015
DOI: 10.1089/vim.2014.0142
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TGF-β1/IL-31 Pathway Is Associated with the Disease Severity of Hepatitis B Virus–Related Liver Cirrhosis

Abstract: The proinflammatory cytokines transforming growth factor beta 1 (TGF-β1) and interleukin (IL)-31 have been implicated in tissue injury. However, whether TGF-β1/IL-31 are stimulated and elevated in response to liver injury that leads to fibrogenesis in hepatitis B virus-related liver cirrhosis (HBV-LC) remains unclear. To investigate the association between TGF-β1/IL-31 and stages of chronic HBV infection, serum TGF-β1, IL-9, IL-10,IL-17, IL-22, IL-23, IL-31, IL-33, and IL-35 were determined among patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
1
30
1
Order By: Relevance
“…Recently, Ming et al found that the upregulation of the TGF-β1/IL-31 pathway is associated with disease severity in LC-B, since elevated serum TGF-β1 and IL-31 levels were positively associated with albumin, alpha-fetoprotein, creatinine, white blood cell, and platelet levels among LC-B patients [30]. Furthermore, TGF-β1/IL-31 pathway may also play an important role in the pathogenesis of liver injury during chronic HBV infection, since increased activity of the TGF-β1/IL-31 pathway has been found well correlated with the extent of liver injury, disease severity, and nonsurvival among ACLF patients, whereas reduced activity of this pathway has been detected during the recovery from liver injury in CHB cases [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ming et al found that the upregulation of the TGF-β1/IL-31 pathway is associated with disease severity in LC-B, since elevated serum TGF-β1 and IL-31 levels were positively associated with albumin, alpha-fetoprotein, creatinine, white blood cell, and platelet levels among LC-B patients [30]. Furthermore, TGF-β1/IL-31 pathway may also play an important role in the pathogenesis of liver injury during chronic HBV infection, since increased activity of the TGF-β1/IL-31 pathway has been found well correlated with the extent of liver injury, disease severity, and nonsurvival among ACLF patients, whereas reduced activity of this pathway has been detected during the recovery from liver injury in CHB cases [31].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β expression has also been associated to liver fibrosis in HBV-infected patients, but a role in HIV co-infected patients has not been demonstrated 92. Differing from HCV/HIV co-infections, liver fibrosis mediated through apoptosis-related receptors does not seem to play a major role in HBV/HIV co-infection.…”
Section: Co-infection With Viral Hepatitismentioning
confidence: 98%
“…Studies have shown that HBV and its viral proteins are at least partially responsible for over-activation of TGF-β signaling in HBV-related HCC [13, 14]. Lee et al found that HBx enhanced phosphorylation of pSmad2/3C by binding with Smad4 and amplified TGF-β signal pathway in several HCC cell lines, which led to the enhanced transcriptional activation of TGF-β-responsive genes [15].…”
Section: Introductionmentioning
confidence: 99%